A Comprehensive Survey And Study Of Tilapia Aquaculture In Malaysia With Emphasis On Production Strategies And Feed Inputs - Teh , Sih Win (2010)

(untitled)
A survey was conducted over a period of 10 months between November 2006 and August 2007 to collect data on tilapia culture practised in Malaysia with emphasis on farming systems and feed inputs. A total of 104 farmers from eight states comprising Negeri Sembilan, Pahang, Perak, Pulau Pinang, Sabah, Sarawak, Selangor and Terengganu were interviewed. Based on the responses received, major farming systems used in Malaysia were earthen ponds (40%), cage culture (32%) and ex-mining pools (24%).